Ink-philic BOPP (biaxially-oriented polypropylene) film as well as preparation method and application thereof
By using a combination of nuclear titanium dioxide and PE wax dispersant in BOPP film production, the production problems caused by titanium dioxide agglomeration are solved, efficient production and excellent ink adhesion are achieved, and the application scope is expanded.
Patent Information
- Application Number
- CN202411414782.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-11
AI Technical Summary
During the production process of white BOPP membrane, the agglomeration of titanium dioxide leads to problems such as clogging of the filter mesh, low production efficiency, unqualified film quality and poor ink adhesion.
Nuclear titanium dioxide is used to replace titanium dioxide, and PE wax and dispersant are used in the polypropylene system for uniform dispersion, which improves the flowability of the masterbatch and reduces the filter pressure value, reduces agglomeration, and forms a porous structure to improve porosity and ink adhesion. .
It effectively reduces the risk of filter clogging, improves production efficiency and film quality, enhances ink adhesion, and widens application areas.
Smart Images

Figure CN119220018A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of organic materials, and in particular to an ink-friendly BOPP film and a preparation method and application thereof. Background Art
[0002] Biaxially oriented polypropylene film (BOPP) is mainly used in ice cream bags, disposable chopstick bags, express bags, beverage wrap-around labels, daily chemical self-adhesive labels, cosmetic masks and other fields (see the attached manual). Figure 1 ). In the production process of white BOPP film, white masterbatch needs to be added to the formula to give the BOPP film a white color. If it is not added, it will be transparent. Foaming masterbatch is also needed to form bubbles inside the BOPP film during the production and stretching process, reducing the density of the finished film and reducing the amount of PP under the premise of the same thickness. However, too much foaming masterbatch may cause uneven thickness of the film or even cause deformation of the film.
[0003] At present, white masterbatch mainly consists of PP, titanium dioxide and a small amount of dispersant. Titanium dioxide is very easy to agglomerate during processing because of its polar surface and small particle size. Among the agglomerated particles, the larger ones will be intercepted by the filter. As the production progresses, the agglomerated particles on one side of the filter become more and more, the mesh openings that are blocked are also increasing, and the remaining unobstructed mesh openings are decreasing. Therefore, the extruder current and the pressure before the mesh will increase. As the extrusion pressure gradually increases, some of the agglomerated particles that were previously intercepted will squeeze through the mesh opening of the filter, forming impurities in the film. The larger impurity particles will cause stress concentration in the film at the particle position, resulting in continuous film breakage during the production process. Impurities that do not cause continuous film breakage will be retained on the surface of the film, affecting the printing effect of the film. In summary, the main problems are as follows: the mesh of the extruder filter is blocked, and the pressure before the filter increases; the current load at the extrusion point is too large, the production energy consumption becomes higher, and the equipment wear becomes larger; the film is easily broken during the production process, resulting in shutdown and production reduction, reduced production efficiency, and waste of production raw materials; impurities appear on the film surface, and the product is unqualified.
[0004] In addition, the produced BOPP film will be printed with ink in the downstream process. Ink adhesion is an important indicator of BOPP film quality. Often the same ink will have different performances on different BOPP films. Therefore, improving the adhesion of its surface to ink is also a key technical improvement direction. Summary of the invention
[0005] The present invention provides an ink-friendly BOPP film, a preparation method and application thereof. The white masterbatch used has high fluidity and low filter pressure value, is not easy to clog the filter screen during the preparation of the BOPP film, and improves production efficiency. The prepared BOPP film has low density, less impurities, high surface roughness and high ink adhesion.
[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide an ink-friendly BOPP film, comprising the following components in parts by weight:
[0007] Polypropylene A: 75 parts to 85 parts;
[0008] White masterbatch: 10-17 parts;
[0009] Foaming masterbatch: 3-8 parts;
[0010] The white masterbatch comprises the following components in parts by weight:
[0011] Polypropylene B: 30-50 parts;
[0012] Nuclear titanium dioxide: 50-70 parts;
[0013] PE wax: 5-10 parts;
[0014] Dispersant: 0.5-2 parts;
[0015] Blue pigment: 0.03 parts to 1 parts.
[0016] By adopting the above scheme, the present application adopts nuclear titanium dioxide in the white masterbatch. The nuclear titanium dioxide is evenly dispersed in the polypropylene system by using PE wax and dispersant, and is not easy to agglomerate, thereby improving the fluidity of the masterbatch and reducing the filter pressure value. The pressure in front of the filter screen can be reduced, the current load can be reduced, and the continuous film breaking time can be delayed during the preparation of the BOPP film. At the same time, the nuclear titanium dioxide can replace part of the foaming masterbatch, so that porous gaps can be formed inside the BOPP film, the porosity can be increased, the film density can be significantly reduced, and the amount of foaming masterbatch added can be reduced. Due to the special core-shell structure of the nuclear titanium dioxide, the prepared BOPP film has a high surface roughness, uniform particle dispersion, and high ink adhesion, which can expand the application field.
[0017] As a preferred solution, the particle size D50 of the core titanium dioxide is 300-600nm.
[0018] As a preferred embodiment, the dispersant is at least one of a titanate coupling agent, an aluminate coupling agent, an aluminozirconate coupling agent, a silane coupling agent, and stearic acid.
[0019] As a preferred solution, the mass ratio of the polypropylene B to the core titanium dioxide is 4:6.
[0020] As a preferred embodiment, the blue pigment includes at least one of ultramarine, phthalocyanine blue, cobalt blue, cobalt chrome blue and iron blue.
[0021] By adopting the above scheme, a trace amount of blue pigment can improve the hue of the white masterbatch. By utilizing the blue-white color, the prepared film can be visually closer to white, which can reduce the amount of white masterbatch added and save costs.
[0022] In order to solve the above technical problems, the second purpose of the present invention provides a method for preparing an ink-friendly BOPP film, comprising the following steps: respectively putting white masterbatch, foaming masterbatch and polypropylene into their respective blanking units, entering each layer of extruder, and sequentially undergoing blanking, extrusion, casting, longitudinal stretching, transverse stretching, traction, corona, and winding systems to prepare the BOPP film.
[0023] As a preferred solution, the extruder temperature is controlled at 200-250°C.
[0024] As a preferred embodiment, the longitudinal stretching ratio is 4-5, the transverse stretching ratio is 6-9, and the corona value is 40 dynes.
[0025] As a preferred embodiment, the method for preparing the white masterbatch comprises the following steps:
[0026] (1) Putting nuclear titanium dioxide, PE wax, dispersant, and blue pigment into a high-speed stirring device, and when the temperature of the stirrer rises to a preset temperature of 40-60° C., starting stirring, premixing at a rate of 30-50 r / min for 0-15 min, then adding polypropylene into the high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 60-80° C., starting stirring, mixing at a rate of 120-150 r / min for 5-20 min, and fully mixing to obtain a premix;
[0027] (2) Turn on the pelletizer, add the premix into the extruder, and prepare white masterbatch through extrusion, cooling, and pelletizing.
[0028] As a preferred embodiment, in step (2) of the method for preparing white masterbatch, the extrusion temperature is controlled at 160-220°C.
[0029] In order to solve the above technical problems, the third object of the present invention provides an ink-philic BOPP film for use in the preparation of food packaging bags, disposable product packaging bags, express bags, daily chemical self-adhesive labels or cosmetic masks.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present application adopts nuclear titanium dioxide to replace titanium dioxide in the white masterbatch. Compared with the problem of easy agglomeration of titanium dioxide, the nuclear titanium dioxide of the present application is evenly dispersed in the polypropylene system by using PE wax and dispersant, and is not easy to agglomerate, which can improve the fluidity of the masterbatch and reduce the filter pressure value. The smaller the filter pressure value, the better, and the lower the value, the more it can pass through the filter. The filter has excellent permeability, which reduces the pressure in front of the filter, reduces the current load, and delays the continuous film breaking time during the preparation of BOPP film, reduces energy consumption, and improves production smoothness.
[0032] 2. The nuclear titanium dioxide added to the white masterbatch of the present application can also replace part of the foaming masterbatch. Since the nuclear titanium dioxide is not easy to agglomerate in the polypropylene system and is evenly dispersed, the nuclear titanium dioxide particles have an irregular structure of small balls covering large balls, so that porous gaps are formed inside the BOPP film, the porosity is increased, and the film density is significantly reduced, which can reduce the amount of foaming masterbatch added. The prepared BOPP film has fewer impurities, higher surface roughness, evenly dispersed particles, high ink adhesion, and superior BOPP performance, which can expand the application field. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 : Specific products for BOPP films used in different fields;
[0034] Figure 2 : A scanning electron microscope image of an ink-friendly BOPP film in Example 2 at a magnification of 1800 times;
[0035] Figure 3 : This is a scanning electron microscope image of the cross section of the sample after the white masterbatch and polypropylene film were prepared in step (2) of Example 2 at a magnification of 1800 times;
[0036] Figure 4 : This is a scanning electron microscope image of the cross section of the sample after the white masterbatch and polypropylene film were prepared in step (2) of Example 2 at a magnification of 4000 times;
[0037] Figure 5 : This is a scanning electron microscope image of the sample cross section at a magnification of 4000 times after the white masterbatch and polypropylene film were prepared in step (2) of Comparative Example 1. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Table 1 - Sources of raw materials used in the examples or comparative examples of this application
[0040]
[0041] Example 1
[0042] A BOPP film with ink affinity comprises 75kg polypropylene, 17kg white masterbatch and 8kg foaming masterbatch, wherein the white masterbatch comprises 50kg polypropylene, 50kg nuclear titanium dioxide, 5kg PE wax, 0.8kg titanate coupling agent, and 0.05kg ultramarine blue, wherein the particle size D50 of the nuclear titanium dioxide is 550nm, the nuclear titanium dioxide is specifically the brand RTR-202 of Foshan Jianfa Ruitong Technology Co., Ltd., and the foaming masterbatch is specifically the brand MB-PF702 product of Kingfa Technology Co., Ltd., and the preparation method thereof comprises the following steps:
[0043] (1) Putting nuclear titanium dioxide, PE wax, titanate coupling agent, and blue pigment into a high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 40° C., start stirring, and pre-mix at a low speed of 40 r / min for 5 min. Then, adding polypropylene into the high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 60° C., start stirring, and mix at a high speed of 120 r / min for 5 min to fully mix them together to obtain a premix;
[0044] (2) starting the pelletizer, adding the premix into the extruder, controlling the extrusion temperature at 160-220° C., and preparing a white masterbatch by extrusion, cooling, and pelletizing;
[0045] (3) The white masterbatch, foaming masterbatch and polypropylene are respectively put into their respective blanking units, and enter the extruders of each layer according to the formula ratio. The temperature of the extruder is controlled at 200-250°C. The BOPP film is prepared through blanking, extrusion, casting, longitudinal stretching, transverse stretching, traction, corona and winding systems in sequence. The longitudinal stretching ratio is 4.8, the transverse stretching ratio is 8, the corona value is 40 dynes, and a BOPP film with a thickness of 60 μm is obtained.
[0046] Example 2
[0047] A BOPP film with ink affinity comprises 80kg polypropylene, 15kg white masterbatch and 5kg foaming masterbatch, wherein the white masterbatch comprises 40kg polypropylene, 60kg nuclear titanium dioxide, 6kg PE wax, 1kg titanate coupling agent, and 0.05kg ultramarine blue, wherein the particle size D50 of the nuclear titanium dioxide is 550nm, the nuclear titanium dioxide is specifically the brand RTR-202 of Foshan Jianfa Ruitong Technology Co., Ltd., and the foaming masterbatch is specifically the brand MB-PF702 product of Kingfa Technology Co., Ltd., and the preparation method thereof comprises the following steps:
[0048] (1) Putting nuclear titanium dioxide, PE wax, titanate coupling agent, and blue pigment into a high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 50° C., stirring is started, and premixing is performed at a low speed of 30 r / min for 10 min. Then, polypropylene is added into the high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 70° C., stirring is started, and high-speed mixing is performed at a speed of 130 r / min for 10 min to fully mix them together to obtain a premix;
[0049] (2) starting the pelletizer, adding the premix into the extruder, controlling the extrusion temperature at 160-220° C., and preparing a white masterbatch by extrusion, cooling, and pelletizing;
[0050] (3) The white masterbatch, foaming masterbatch and polypropylene are respectively put into their respective blanking units, and enter the extruders of each layer according to the formula ratio. The temperature of the extruder is controlled at 200-250°C. The BOPP film is prepared through blanking, extrusion, casting, longitudinal stretching, transverse stretching, traction, corona and winding systems in sequence. The longitudinal stretching ratio is 4.8, the transverse stretching ratio is 8, the corona value is 40 dynes, and a BOPP film with a thickness of 60 μm is obtained.
[0051] Example 3
[0052] A BOPP film with ink affinity comprises 85kg polypropylene, 10kg white masterbatch and 5kg foaming masterbatch, wherein the white masterbatch comprises 30kg polypropylene, 70kg nuclear titanium dioxide, 7kg PE wax, 1.2kg titanate coupling agent, and 0.05kg ultramarine blue, wherein the particle size D50 of the nuclear titanium dioxide is 550nm, the nuclear titanium dioxide is specifically the brand RTR-202 of Foshan Jianfa Ruitong Technology Co., Ltd., and the foaming masterbatch is specifically the brand MB-PF702 product of Kingfa Technology Co., Ltd., and the preparation method thereof comprises the following steps:
[0053] (1) Putting nuclear titanium dioxide, PE wax, titanate coupling agent, and blue pigment into a high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 50° C., starting stirring, and premixing at a low speed of 50 r / min for 15 min, then adding polypropylene into the high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 70° C., starting stirring, and mixing at a high speed of 150 r / min for 15 min, so that they are fully mixed and uniformly obtained to obtain a premix;
[0054] (2) starting the pelletizer, adding the premix into the extruder, controlling the extrusion temperature at 160-220° C., and preparing a white masterbatch by extrusion, cooling, and pelletizing;
[0055] (3) The white masterbatch, foaming masterbatch and polypropylene are respectively put into their respective blanking units, and enter the extruders of each layer according to the formula ratio. The temperature of the extruder is controlled at 200-250°C. The BOPP film is prepared through blanking, extrusion, casting, longitudinal stretching, transverse stretching, traction, corona and winding systems in sequence. The longitudinal stretching ratio is 4.8, the transverse stretching ratio is 8, the corona value is 40 dynes, and a BOPP film with a thickness of 60 μm is obtained.
[0056] Example 4
[0057] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the BOPP film includes 82 kg of polypropylene, 15 kg of white masterbatch, and 3 kg of foaming masterbatch.
[0058] Example 5
[0059] A BOPP film that is ink-friendly, wherein the steps of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the particle size D50 of the core titanium dioxide in the white masterbatch is 550 nm, and the core titanium dioxide is specifically the brand RTR-201 of Foshan Jianfa Ruitong Technology Co., Ltd.
[0060] Example 6
[0061] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the particle size D50 of the core titanium dioxide in the white masterbatch is 380 nm, and the core titanium dioxide is specifically the brand RTR-203 of Foshan Jianfa Ruitong Technology Co., Ltd.
[0062] Example 7
[0063] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the foaming masterbatch is specifically the brand F2000 of Guangdong Meilian New Materials Co., Ltd.
[0064] Example 8
[0065] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment and process parameters applicable to each step are the same as those in Example 2, except that the foaming masterbatch is specifically the brand PF97N of Schulman Plastics Company of the United States.
[0066] Example 9
[0067] A BOPP film that is ink-friendly, wherein the steps of the preparation method and the reagents, equipment and process parameters applicable to each step are the same as those in Example 2, except that the ultramarine blue in the white masterbatch is replaced by an equal amount of polypropylene.
[0068] Comparative Example 1
[0069] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the core titanium dioxide in the white masterbatch is replaced by an equal amount of titanium dioxide, and the particle size D50 of the titanium dioxide is 380 nm.
[0070] Comparative Example 2
[0071] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the PE wax in the white masterbatch is replaced by an equal amount of polypropylene.
[0072] Comparative Example 3
[0073] A BOPP film that is ink-friendly, wherein each step of the preparation method and the reagents, equipment and process parameters applicable to each step are the same as those in comparative example 1, except that the PE wax in the white masterbatch is replaced by an equal amount of polypropylene.
[0074] Comparative Example 4
[0075] A BOPP film that is ink-friendly, and the steps of the preparation method thereof and the reagents, equipment, and process parameters applicable to each step are the same as those in Example 2, except that the white masterbatch includes 86kg of polypropylene, 20kg of nuclear titanium dioxide, 1kg of titanate coupling agent, and 0.05kg of ultramarine blue, the particle size D50 of the nuclear titanium dioxide is 550nm, the nuclear titanium dioxide is specifically the brand RTR-202 of Foshan Jianfa Ruitong Technology Co., Ltd., and the foaming masterbatch is specifically the brand MB-PF702 product of Kingfa Technology Co., Ltd.
[0076] Table 2 - Components and contents in the examples and comparative examples of the present application
[0077]
[0078]
[0079] Performance testing
[0080] 1. The density of the white masterbatch obtained in step (2) of the embodiment or comparative example was tested. The test results are shown in Table 3 below.
[0081] 2. The white masterbatch obtained in step (2) of the embodiment or comparative example was tested for melt index according to GB / T 3682-2000 "Determination of mass flow rate and volume flow rate of thermoplastic melts". The test conditions were 230°C and the load was 2.16 kg. The test results are shown in Table 3 below.
[0082] 3. The white masterbatch obtained in step (2) of the embodiment or comparative example was tested for filter pressure value according to EU standard EN 13900-5:2005 "Pigments and extenders-Methods of dispersion and assessment ofdispersibility in plastics-Part 5:Determination by filter pressure value test". The testing instrument is a pressure filtration performance tester of Dongguan Baopin Precision Instrument Co., Ltd., model BP-8186-B. The test results are shown in Table 3 below.
[0083] 4. In the biaxially oriented film production process of the BOPP film of the embodiment or the comparative example in step (3), under the premise of the same production speed of 380 m / min, the extruder current after the extruder is turned on for 4 hours, the pressure in front of the filter screen after the extruder is turned on for 4 hours, and the time from the start of the machine to continuous film breaking are observed and counted. The statistical results are shown in Table 4 below.
[0084] 5. The BOPP film prepared in Example 2 was tested by scanning electron microscope. The test results are as follows: Figure 2 As shown; at the same time, the white masterbatch prepared in step (2) of Example 2 and Comparative Example 1 was subjected to film drawing with polypropylene, and then subjected to scanning electron microscopy detection, which specifically includes the following steps:
[0085] (1) The cast film production process uses a three-layer co-extrusion method. A small co-extrusion experimental machine, model LYE-1, produced by Hefei Puliang Technology Co., Ltd. is used. Polypropylene and white masterbatch are mixed in a mass ratio of 5:1 and fed into the blanking system of the core layer extruder. The upper and lower surface layer extruders are fed with 100% polypropylene. When the temperature of the three extruders rises to 220°C, thick sheets are extruded. The extrusion speed is adjusted to adjust the thickness of the thick sheet to 1.2 cm. The thick sheet is wound and cut into 13×13 cm squares for the next step of biaxial stretching.
[0086] (2) A BSE biaxial tensile testing machine, model BSE-II, from Hefei Puliang Technology Co., Ltd. was used. The temperature of the stretching zone was set to 200°C. The previously cut sample was placed in the sample chamber, and the sample chamber was moved into the stretching zone. The surface temperature of the sample was observed. When the sample temperature reached 160°C, stretching began. The longitudinal stretching ratio was set to 4 times, the transverse stretching ratio was set to 5 times, and the stretching speed was 30 cm / min. After the stretching was completed, the obtained film was about 60 μm. The film was tested by scanning electron microscopy. The test results are as follows: Figure 3-5 shown.
[0087] in, Figure 3-4 The scanning electron microscope image of the cross-section after film drawing of the white masterbatch prepared in Example 2 is shown. Without adding the foaming masterbatch, the white masterbatch is doped with core titanium dioxide raw material. The core titanium dioxide is a special core-shell structure made of titanium dioxide coated with inorganic powder. Due to the internal support of the inorganic powder, the titanium dioxide on the surface will not collapse inward and will not easily agglomerate with each other, and can be evenly dispersed in the film. Therefore, the particle size is small, which helps to improve the morphology of the prepared film. During the film stretching process, the molecular chains of polypropylene are elongated due to the stretching process, and the polypropylene molecular chains slide against each other, while the granular structure of the core titanium dioxide inorganic powder cannot be extended with the stretching, so at the position of the inorganic particles, some stretched and deformed polypropylene molecular chains will separate from the core titanium dioxide, thereby causing holes. At the same time, the appearance structure of nuclear titanium dioxide is not a relatively round and regular sphere like titanium dioxide, but an irregular structure of small balls covering large balls. Its compatibility with polypropylene resin is also different from that of titanium dioxide. Therefore, during the stretching process, nuclear titanium dioxide is more likely to separate from the polypropylene molecular chain, thereby generating holes, which ultimately makes the film cross-section porosity higher, forming a loose and porous structure, which can significantly reduce the density of the film. Figure 2 As shown, the particle size of the core titanium dioxide in the prepared BOPP film is evenly dispersed, and the particle size is uniformly small, less agglomerated, and has a higher porosity, and the density of the prepared film is significantly reduced.
[0088] Figure 5 This is a scanning electron microscope image of the cross-section of the white masterbatch prepared in Example 1 after film drawing. The white masterbatch is doped with titanium dioxide raw material, and some agglomerated titanium dioxide is intercepted and filtered out by the filter during the preparation process. The particle size of the raw titanium dioxide is smaller than that of the core titanium dioxide in Example 2. The porosity in the film is relatively low, there are fewer holes, and the density of the film is significantly higher than that of Example 2.
[0089] 6. The density and surface roughness of the BOPP films prepared in the examples or comparative examples were tested. The surface roughness was tested in accordance with GB / T 14234-1993 "Surface Roughness of Plastic Parts". The test instrument was a surface roughness measuring instrument made by Mitutoyo, Japan, model SJ-301. The test results are shown in Table 4 below.
[0090] 7. Count the number of impurities in the BOPP film prepared in the embodiment or comparative example, and observe the number of impurities per 1m 2 The number of impurities contained in the area, the statistical results are shown in Table 4 below.
[0091] 8. The BOPP film prepared in the embodiment or comparative example is subjected to ink tape tearing and shedding grid number detection, comprising the following steps:
[0092] (1) Use the flexographic colorimeter (model KY160) of Dongguan Liede Technology Co., Ltd., drip ink on the rubber roller, turn on the colorimeter, start to evenly distribute the ink, set the ink distribution speed to 550r / min, and set the ink distribution time to 30s. After the ink distribution is completed, cut the film into the size of an A4 paper sample, clamp it flat on the printing sample roller, with the corona side of the film facing up, adjust the printing speed to 10r / min, and click Print to complete the printing;
[0093] (2) Lay the film with the printed surface facing up on a flat surface and fix it with tape on all sides. Use a pencil to draw 100 small grids on the ink surface at equal intervals, 10 in each direction. Use 3M brand 600 transparent tape to stick it on the ink. Tear off the tape vigorously and observe the number of grids where the ink falls off. The fewer the number of grids that fall off, the higher the ink adhesion. The test results are shown in Table 4 below.
[0094] 9. The whiteness of the BOPP films prepared in the examples and comparative examples was tested according to GB / T 2913-1982 "Test Method for Whiteness of Plastics" using a multifunctional whiteness meter (model BDG584) from Biaogeda Precision Instruments (Guangzhou) Co., Ltd. The test results are shown in Table 4 below.
[0095] Table 3 - Performance test results of white masterbatch prepared in the present application examples and comparative examples
[0096]
[0097] As shown in Table 3, the nuclear titanium dioxide added to the white masterbatch in Examples 1-3 is evenly dispersed in the polypropylene system, and the nuclear titanium dioxide is not easy to agglomerate, and the melt index is high, indicating good fluidity. The filter pressure value reflects the degree to which the white masterbatch agglomerates at the filter screen and blocks the filter screen when passing through the extruder filter screen. The smaller the filter pressure value, the more it can pass through the filter screen, the better the filter screen is, and the filter screen is not easy to block the filter screen. Since the density of nuclear titanium dioxide is lower than that of titanium dioxide, the density of the masterbatch prepared under the premise of equal addition amount is relatively low. However, the titanium dioxide added to the white masterbatch in Comparative Example 1 is easy to agglomerate, resulting in a low melt index of the masterbatch, low fluidity, and a significantly higher filter pressure value, which is easy to block the filter screen of the extruder.
[0098] Table 4 - Performance test results of BOPP films prepared in the present application examples and comparative examples
[0099]
[0100]
[0101] As shown in Table 4, the BOPP film prepared in Example 2 has a lower density. This is because the nuclear titanium dioxide is evenly dispersed in the BOPP film, the particle size is small, and the fluidity of the film melt is high. When the extruder passes through the filter screen, it is smooth, and there are fewer impurities that will not cause blockage, which effectively delays the continuous film breaking time. The addition of nuclear titanium dioxide helps to increase the porosity of the film and form a porous internal space structure. This is caused by the special structure of nuclear titanium dioxide. Nuclear titanium dioxide is a special core-shell structure made of titanium dioxide coated inorganic powder. The shape structure is not a relatively round and regular sphere like titanium dioxide, but an irregular structure of small balls covering large balls. At the position of the inorganic particles, some stretched and deformed polypropylene molecular chains will separate from the nuclear titanium dioxide, thereby causing holes, thereby reducing the density of the film. In Comparative Example 1, titanium dioxide is doped in the BOPP film as a white pigment. Due to the high surface polarity and small particle size, it is easy to agglomerate, resulting in low fluidity of the white masterbatch. The small particle size also makes the film have a low porosity, a relatively high density, and a low surface roughness. In addition, large agglomerated particles are formed in the film, which is easy to produce impurities. The BOPP film of Example 2 has a high surface roughness and uniform surface particle dispersion, which is conducive to the increase of ink adhesion. The added nuclear titanium dioxide RTR-202 has a good ink affinity effect, so that the ink shedding test results in Example 2 are significantly better than those in Comparative Example 1.
[0102] As shown in Table 4, by comparing the schemes of Example 2 and Comparative Examples 1-3, it can be seen that Comparative Example 2 does not add PE wax compared to Example 2, resulting in uneven dispersion of the nuclear titanium dioxide particles in the film system. It can be found that the film melt is greatly increased in the current and pre-net pressure of the extruder, indicating that the particles in the melt are prone to agglomeration. The surface roughness of the film is slightly increased, the number of impurities generated by the film increases, and the size distribution of more particles on the surface of the film is uneven, which leads to the easy occurrence of ink shedding during the flat printing of the film, and the ink adhesion is greatly reduced. Compared with Comparative Example 1, Comparative Example 3 does not add PE wax. It can be found that the current and pre-net pressure of the film melt in the extruder increase, and the number of film impurities increases, the surface roughness of the film increases, and the uneven distribution of particles leads to low ink adhesion.
[0103] As shown in Table 4, compared with Example 2, the core titanium dioxide content of the film of Comparative Example 4 is reduced by two-thirds, and PE wax is not added. It can be found that the current and pre-mesh pressure of the film melt in the extruder are relatively small, indicating that the inorganic particles in the melt are evenly dispersed due to their low content and are not easy to agglomerate. However, the density of the prepared film is relatively high, and the whiteness and ink adhesion are significantly low, which cannot meet the application requirements.
[0104] As shown in Table 4, the BOPP films of Examples 2, 5-6 respectively use white masterbatches containing RTR-201, RTR-202, and RTR-203 nuclear titanium dioxide. The final test shows that the ink affinity of the film of Example 2 is the best, indicating that RTR-202 nuclear titanium dioxide is beneficial to improving the printing effect of BOPP film, improving ink adhesion, and the film has a high whiteness.
[0105] As shown in Table 4, compared with Example 9, the trace amount of blue pigment in Example 2 can improve the hue of the white masterbatch. The blue-white color makes the prepared film visually closer to white, which can reduce the amount of white masterbatch added and save costs.
[0106] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A BOPP film with ink affinity, characterized in that: It includes the following components by weight: Polypropylene A: 75 parts to 85 parts; White masterbatch: 10-17 parts; Foaming masterbatch: 3-8 parts; The white masterbatch comprises the following components in parts by weight: Polypropylene B: 30-50 parts; Nuclear titanium dioxide: 50-70 parts; PE wax: 5-10 parts; Dispersant: 0.5-2 parts; Blue pigment: 0.03 parts to 1 parts.
2. The ink-philic BOPP film according to claim 1, characterized in that: The particle size D50 of the core titanium dioxide is 300-600nm.
3. The ink-loving BOPP film according to claim 1, characterized in that: The dispersant is at least one of a titanate coupling agent, an aluminate coupling agent, an aluminozirconate coupling agent, a silane coupling agent, and stearic acid.
4. The ink-philic BOPP film according to claim 1, characterized in that: The mass ratio of the polypropylene B to the core titanium dioxide is 4:
6.
5. The ink-philic BOPP film according to claim 1, characterized in that: The blue pigment includes at least one of ultramarine, phthalocyanine blue, cobalt blue, cobalt chrome blue and iron blue.
6. A method for preparing an ink-philic BOPP film as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: The white masterbatch, foaming masterbatch and polypropylene are respectively put into their respective blanking units and enter each layer of the extruder. BOPP film is prepared through blanking, extrusion, sheet casting, longitudinal stretching, transverse stretching, traction, corona and winding systems.
7. The method for preparing an ink-friendly BOPP film according to claim 6, characterized in that: The preparation method of the white masterbatch comprises the following steps: (1) Putting nuclear titanium dioxide, PE wax, dispersant, and blue pigment into a high-speed stirring device, and when the temperature of the stirrer rises to a preset temperature of 40-60° C., starting stirring, premixing at a rate of 30-50 r / min for 0-15 min, then adding polypropylene into the high-speed stirrer, and when the temperature of the stirrer rises to a preset temperature of 60-80° C., starting stirring, mixing at a rate of 120-150 r / min for 5-20 min, and fully mixing to obtain a premix; (2) Turn on the pelletizer, add the premix into the extruder, and prepare white masterbatch through extrusion, cooling, and pelletizing.
8. The method for preparing an ink-philic BOPP film according to claim 7, characterized in that: In step (2) of the method for preparing white masterbatch, the extrusion temperature is controlled at 160-220°C.
9. The method for preparing an ink-friendly BOPP film according to claim 6, characterized in that: The longitudinal stretching ratio is 4-5, the transverse stretching ratio is 6-9, and the corona value is 40 dynes.
10. Use of the ink-philic BOPP film according to any one of claims 1 to 5 in the preparation of food packaging bags, disposable product packaging bags, express bags, daily chemical self-adhesive labels or cosmetic facial masks.
Citation Information
Patent Citations
Production process method of high-performance color master batch modified material
CN117050346A
Biaxially oriented polypropylene electrical membrane and preparation method thereof
CN117866255A
High-concentration white polyolefine agglomerate and its prepn process
CN1487012A
Composite material of inorganic nonmetallic mineral loaded with titania layer, preparation process and use thereof
US20130052243A1
Cited By
Preparation process of BOPP white film
CN119795419A
Process for the preparation of a bopp white film
CN119795419B
Preparation method of polypropylene film for label
CN119798756B